Sustainable Use of Forest Biomass for Energy - Röser, Dominik (Springer, 2017)
With the large-scale utilization of forest biomass for energy still in its infancy, there is an urgent need to understand the short- and long-term consequences of intensive forest biomass harvesting - both on the forest ecosystem and on forest economics.